Designing and Evaluation of Glimepiride Ficus glomerata Fruit Mucilage Matrix Transdermal Patches - Abdul Ahad, Hindustan; Kiranmaye, N.; Yasmeen, Rubiya; Ruksana, H.; Muneer, S. (Asian Journal of Chemistry, 2010)
The main object of the present investigation is to develop transdermal patches of Glimepiride with Ficus glomerata fruit mucilage and to study the permeability patterns. Transdermal patches were prepared by solvent evaporation technique. The prepared patches were evaluated for physicochemical characteristics viz., thickness, mass and drug content, which were uniform in prepared batches. The study proved that Glimepiride can be developed as a transdermal patch with Ficus glomerata fruit mucilage. In vitro permeation studies were performed using Albino rat abdominal skin as the permeating membrane in Keshary-Chien cell.